Efektivitas Pelaksanaan Rencana Pengelolaan Lingkungan dan Rencana Pemantauan Lingkungan (RKL-RPL) Pertambangan Batubara PT. Adaro Indonesia di Kabupaten Tabalong, Provinsi Kalimantan Selatan - Iid Moh Abdul Wahid; Budhi Gunawan; Teguh Husodo (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2016)
Environmental Impact Assessment (EIA) is a planning and preventive document. This is one of the environmental protection and management efforts in order to prevent environmental damage. In Tabalong there are more than 30 business agent and / or activities that have made EIA mining, 24 of which are mining operations. PT Adaro Indonesia is the largest company in Tabalong with a concession area of 35,536 hectares and a production capacity of 80 million tons / year and has had environmental documents (EIA) and Environmental Permit. During this time PT. Adaro Indonesia, in operation, has been carrying out management and environmental monitoring (RKL-RPL) in the area of mining, but on the other hand the number of public complaints due to alleged pollution and / or destruction of the environment by the activity of PT. Adaro Indonesia remains the case that many questioned the implementation of its EIA (RKL-RPL). This research aims to study the effectiveness and the factors that affect the implementation of the EIA (RKL-RPL) coal mining PT. Adaro Indonesia. This research was conducted using qualitative-quantitative approach (mix method) with concurrent triangulation strategy model. The research data obtained through observation, interviews, questionnaires and review of the literature. The results showed that the implementation of the RKL-RPL PT. Adaro Indonesia is said to be effective with each aspect of obedience (compliance) 95%, institutional 91.67%, Monitoring (supervision) 92.86% and handling public complaints66.67%. The factors that influence the effectiveness of the implementation of the EIA PT. Adaro Indonesia is communication and coordination, resources (staff, skills, information, authority, and facilities), regulation and government policy, funding, enforcement and legal certainty (incentives / disincentives), and bureaucratic institutional structure.